Protective Effect of Esculin on Streptozotocin-Induced Diabetic Renal Damage in Mice - Kang, Ki Sung; Lee, Woojung; Jung, Yujung; Lee, Ji Hwan; Lee, Seungyong; Eom, Dae-Woon; Jeon, Youngsic; Yoo, Hye Hyun; Jin, Ming Ji; Song, Kyung Il; Kim, Won Jun; Ham, Jungyeob; et al. (AMER CHEMICAL SOC, 2014)
The present study investigated the presence and mechanism of esculin-mediated renoprotection to assess its therapeutic potential. Esculin was orally administered at 20 mg/kg/day for 2 weeks to streptozotocin-induced diabetic mice, and its effects were compared with those of the vehicle in normal and diabetic mice. After oral administration of esculin to mice, the concentrations of esculin and esculetin in blood were 159.5 +/- 29.8 and 9.7 +/- 4.9 ng/mL at 30 min, respectively. Food and water intake were significantly increased in the diabetic mice compared to normal mice but attenuated in mice receiving esculin. The elevated blood glucose level and hepatic glucose-6-phosphatase expression were significantly reduced in esculin-treated diabetic mice, supporting the antidiabetic effect of esculin. Esculin also increased the uptake of glucose and induced the insulin-evoked phosphorylation of insulin receptor, Akt, and glycogen synthase kinase 3 beta in C2C12 myotubes, indicating a potential for improvement of insulin sensitivity. In addition, esculin lessened the elevated blood creatinine levels in diabetic mice and ameliorated diabetes-induced renal dysfunction by reducing caspase-3 activation in the kidney. Data support the beneficial effect of esculin against diabetes and oxidative stress-related inflammatory processes in the kidney.
Keywords: OXIDATIVE STRESS; NEPHROPATHY; ESCULETIN; APOPTOSIS; CELLS; MODEL; COMPLICATIONS; INDUCTION; COUMARINS